Pelatihan Pemeliharaan Kesehatan Gigi dan Mulut Sejak Dini di Panti Asuhan Kota Palembang - Hanum, Nur Adiba; Ismalayani, Ismalayani; Wahyuni, Sri (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2023)
the pandemic, dental health interventions in the community directly in the field could not be carried out in connection with breaking the chain of transmission of Covid 19. Now that field activities have been allowed in the community, we are conducting dental health interventions at the Marfuah Orphanage in Palembang based on our assessment in February of 2020 before the pandemic, the dental hygiene of the children at the Marfu'ah Palembang Orphanage was still low, with an average plaque score of 2.8 (bad criteria). Plaque is the main cause of caries disease. The goal of PKM is that the children of the Marfu'ah Palembang orphanage are able to care for their teeth independently to get optimal dental and oral health. The targets were 10 orphans and 40 orphans. The training method for teaching theory and skills is through lectures, games, demonstrations, video screenings and simulations. The results after the activity were an increase in knowledge about daily dental care in 90% of children who had good knowledge and only 10% of children had moderate knowledge, there was also an increase in brushing skills properly as many as 92.5% of children, and there was an increase in the level of oral hygiene in children with an average plaque score of 0.75 (good criteria), then 10 orphanage caregivers can be empowered as a companion, supervisor and control of children's dental and oral health.